Understanding climate refugees from educators’ perspectives: Social studies teachers’ views - Leyla Donmez Bayrakci; Fatih Ozdemir (PLoS ONE, 2026)
This study aimed to examine social studies teachers’ knowledge, attitudes, and approaches regarding the concept of climate refugees. Employing a phenomenological design within qualitative research, semi-structured interviews were conducted with volunteer social studies teachers from various provinces in Turkey. The data were analyzed through content analysis and rted with direct quotations from participants. Although their knowledge on the subject was limited, social studies teachers demonstrated sensitivity toward climate refugees and made efforts to address these gaps. They attributed the emergence of climate refugees to human activities, particularly political decisions. While they believed that citizenship could be granted to climate refugees under appropriate conditions, they expressed caution due to current refugee-related challenges. The teachers emphasized the necessity of systematically integrating climate refugee issues into the curriculum, raising teachers’ awareness, and adopting practical, empathy-based teaching methods.